AI Adoption for Productivity Tax Consultant: A Literature Review - Diandra Naufal Ramadhan; Emha Rizky Isnaini (www.amertainstitute.com, 2025)
The rapid adoption of Artificial Intelligence (AI) has significantly transformed the professional services sector, particularly in tax consultancy. This literature review aims to demonstrate that AI integration enhances the productivity of tax consultants by streamlining routine tasks and enabling more strategic decision-making. The study synthesizes findings from peer-reviewed articles, case studies, and industry reports published over the past decade, focusing on the implementation of AI technologies such as machine learning, natural language processing, and robotic process automation within tax consulting practices. The analysis reveals that AI tools substantially reduce the time spent on manual data processing, minimize human errors, and increase the speed and accuracy of tax reporting. These improvements allow consultants to allocate more time to value-added services, such as client advisory and tax planning, thereby boosting overall efficiency and service quality. Moreover, AI enables consultants to handle larger volumes of data, offering deeper insights and faster responses to client needs. Despite these advantages, the literature also highlights several challenges, including data privacy concerns, technological resistance, and the need for continuous upskilling. Addressing these issues is critical for maximizing AI's potential in the consulting domain. This review contributes to the growing knowledge of AI's role in the digital transformation of professional services. It offers valuable insights for tax consulting firms seeking to enhance their productivity through AI adoption. It underscores the strategic importance of embracing technology to remain competitive in a rapidly evolving industry.